(x+4)(x-3)(x+2)=

Simple and best practice solution for (x+4)(x-3)(x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+4)(x-3)(x+2)= equation:


Simplifying
(x + 4)(x + -3)(x + 2) = 0

Reorder the terms:
(4 + x)(x + -3)(x + 2) = 0

Reorder the terms:
(4 + x)(-3 + x)(x + 2) = 0

Reorder the terms:
(4 + x)(-3 + x)(2 + x) = 0

Multiply (4 + x) * (-3 + x)
(4(-3 + x) + x(-3 + x))(2 + x) = 0
((-3 * 4 + x * 4) + x(-3 + x))(2 + x) = 0
((-12 + 4x) + x(-3 + x))(2 + x) = 0
(-12 + 4x + (-3 * x + x * x))(2 + x) = 0
(-12 + 4x + (-3x + x2))(2 + x) = 0

Combine like terms: 4x + -3x = 1x
(-12 + 1x + x2)(2 + x) = 0

Multiply (-12 + 1x + x2) * (2 + x)
(-12(2 + x) + 1x * (2 + x) + x2(2 + x)) = 0
((2 * -12 + x * -12) + 1x * (2 + x) + x2(2 + x)) = 0
((-24 + -12x) + 1x * (2 + x) + x2(2 + x)) = 0
(-24 + -12x + (2 * 1x + x * 1x) + x2(2 + x)) = 0
(-24 + -12x + (2x + 1x2) + x2(2 + x)) = 0
(-24 + -12x + 2x + 1x2 + (2 * x2 + x * x2)) = 0
(-24 + -12x + 2x + 1x2 + (2x2 + x3)) = 0

Combine like terms: -12x + 2x = -10x
(-24 + -10x + 1x2 + 2x2 + x3) = 0

Combine like terms: 1x2 + 2x2 = 3x2
(-24 + -10x + 3x2 + x3) = 0

Solving
-24 + -10x + 3x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 10x-7y=-16 | | -2x-3y=30 | | C+C-4C=0 | | 2x+3x+2=-4(3-x) | | 4-(5-x)=2(4-x) | | 30-4x=x | | (.5)32t^2+16t=320 | | 2(7+9)(7+9)2=x | | 15b^2+32b-7=0 | | 0-1= | | 4a^3+12a-20= | | 3(2z-4)=5(z+3) | | y=0.05x+0.20 | | 5x-7=3x+5 | | 36-(7x+8)=6x+2 | | 4x+9=72 | | 4x-36y=-16 | | 3x+2(4x-9(1-x))=0 | | 30=(x-1)(x+6) | | (5x-8)-(3x+1)=36 | | X+48=220 | | X+73=161 | | X+73=161 | | 75=4e-5(3+2e) | | X+24=83 | | 212222x(232*33)=1111111111 | | X+19=72 | | X+27=36 | | X+18=54 | | X+31=80 | | 5x^2+7x+70=0 | | X+23=63 |

Equations solver categories